An effective tool to support Sustainability Transitions - Albert, Christian (Ökologisches Wirtschaften - Fachzeitschrift, 2008)
Scenarios and Scenario Development Processes can provide valuable contributions to efforts for navigating sustainability transitions. To be effective, scenarios must be perceived as scientifically credible, politically salient, procedurally legitimate and inherently creative.
Keywords: Sustainability Transitions; Participatory Scenario Development